A two-channel slotted sense multiple access protocol for timely and reliable data transmission in industrial wireless sensor networks - Md Abul Kalam Azad; Chi Trung Ngo; Hoon Oh (International Journal of Distributed Sensor Networks)
In designing a real-time MAC protocol for wireless sensor networks, it is desirable to shorten the data acquisition cycle time to satisfy more applications with a tighter time constraint in data collection. To achieve this, one often tries to improve throughput by employing a slot reuse technique. Meanwhile, the slotted sense multiple access protocol that uses a sharable slot was proven to be advantageous for timely and reliable data delivery. However, since the nodes at lower tree levels process more packets or bigger packets with data aggregation, they need a bigger sharable slot. Thus, it is not easy to employ a slot reuse technique due to the size variation of sharable slots. To tackle this problem, we try to reduce the size of an aggregated packet by limiting the number of packets for aggregation using two channels. If every node is allowed to send a single packet during data acquisition cycle time, an equal-sized sharable slot can be allocated to every tree level. It is shown that the proposed approach can reduce data acquisition cycle time significantly while maintaining good reliability in data transmission compared with slotted sense multiple access and also reduce energy consumption greatly compared with another multi-channel MAC protocol.